2018
DOI: 10.1089/jpm.2017.0505
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Consultation in Advanced Chronic Kidney Disease with Pain

Abstract: Pain is common in advanced CKD patients receiving palliative care. While this seems to have been underrecognized, the symptom is potentially amenable to management. We recommend routine assessment of pain burden in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Details of the 40 included studies 14-53 are reported in Table 2 and include data from 963 269 patients from 21 countries. Out of the 40 studies, 17 included a prevalence measure of overall analgesic use, 14,16-18,20,23,25,29,33,36,37,43,45,46,48,49,52 33 included a prevalence measure of one or more specific analgesic drug class, defined as opioid, NSAID, adjuvant, and nonopioid, 14-24,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the 40 included studies 14-53 are reported in Table 2 and include data from 963 269 patients from 21 countries. Out of the 40 studies, 17 included a prevalence measure of overall analgesic use, 14,16-18,20,23,25,29,33,36,37,43,45,46,48,49,52 33 included a prevalence measure of one or more specific analgesic drug class, defined as opioid, NSAID, adjuvant, and nonopioid, 14-24,…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 40 studies, 17 included a prevalence measure of overall analgesic use, 14,16-18,20,23,25,29,33,36,37,43,45,46,48,49,52 33 included a prevalence measure of one or more specific analgesic drug class, defined as opioid, NSAID, adjuvant, and nonopioid, 14-24,26-28,30-47,50 and 18 measured the prevalence of one or more specific analgesic drug, including acetaminophen. 14-16,19,20,22,30,33,36-40,43,48,50,51,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is limited by its retrospective design and a relatively small proportion (~17%) of patients with noncancer diagnosis. Difficulty in predicting the disease trajectories for these patients with end-stage organ failure who opted for conservative treatment and lack of simple referral methods present substantial challenge in initiating ACP discussion in these subjects (26). Although the intervention resulted in an increase in ACP document completion, not all targeted patients agreed to join the ACP program.…”
Section: Discussionmentioning
confidence: 99%